A Nationwide Outbreak of Invasive Pneumococcal Disease in Israel Caused by Streptococcus pneumoniae Serotype 2. (17th November 2020) - Dagan, Ron; Ben-Shimol, Shalom; Benisty, Rachel; Regev-Yochay, Gili; Lo, Stephanie W; Bentley, Stephen D; Hawkins, Paulina A; McGee, Lesley; Ron, Merav; Givon-Lavi, Noga; Valinsky, Lea; Rokney, Assaf
Abstract: Background: Invasive pneumococcal disease (IPD) caused by Streptococcus pneumoniae serotype 2 (Sp2) is infrequent. Large-scale outbreaks were not been reported following pneumococcal conjugate vaccine (PCV) implementation. We describe a Sp2 IPD outbreak in Israel, in the PCV13 era, with focus on Sp2 population structure and evolutionary dynamics. Methods: The data were derived from a population-based, nationwide active surveillance of IPD since 2009. PCV7/PCV13 vaccines were introduced in July 2009 and November 2010, respectively. Sp2 isolates were tested for antimicrobial susceptibility, multilocus sequence typing, and whole-genome sequencing (WGS) analysis. Results: Overall, 170 Sp2 IPD cases were identified during 2009–2019; Sp2 increased in 2015 and caused 6% of IPD during 2015–2019, a 7-fold increase compared with 2009–2014. The outbreak was caused by a previously unreported molecular type (ST-13578), initially observed in Israel in 2014. This clone caused 88% of Sp2 during 2015–2019. ST-13578 is a single-locus variant of ST-1504, previously reported globally including in Israel. WGS analysis confirmed clonality among the ST-13578 population. Single-nucleotide polymorphism–dense regions support a hypothesis that the ST-13578 outbreak clone evolved from ST-1504 by recombination. All tested strains were penicillin-susceptible (minimum inhibitory concentration <0.06 μg/mL). The ST-13578 clone was identified almost exclusively (99%) in the Jewish population and was mainly distributed in 3 of 7 Israeli districts. The outbreak is still ongoing, although it began declining in 2017. Conclusions: To the best of our knowledge, this is the first widespread Sp2 outbreak since PCV13 introduction worldwide, caused by the emerging ST-13578 clone. Abstract : We report on the first large-scale pneumococcal serotype-2 invasive disease in the post–pneumococcal conjugate vaccine era caused by a novel clone (ST-13578). This emphasizes the ability of nonvaccine serotypes not expected to be included in the next-generation vaccine to cause significant morbidity.